Plasma prohepcidin levels in patients with chronic viral hepatitis: relationship with liver fibrosis - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2010)
Objectives Iron is deemed to play a crucial role in the pathophysiology of liver damage in patients with chronic viral hepatitis. Hepcidin has recently emerged as the key hormone in the regulation of iron balance and recycling. We assessed plasma prohepcidin levels in patients with chronic viral hepatitis and investigated the association of this molecule with iron parameters, histologic activity index, and liver fibrosis scores. Methods We enrolled 35 patients with chronic hepatitis C, 27 with chronic hepatitis B, and 21 healthy controls. Plasma levels of prohepcidin were measured by enzyme-linked immunosorbent assay. Results Mean prohepcidin levels were significantly lower in patients with chronic hepatitis B than in those with chronic hepatitis C (P < 0.001) and healthy comparison controls (P < 0.05). In patients with chronic hepatitis C, prohepcidin was independently associated with liver fibrosis scores (beta = -0.009, standard error = 0.003, P < 0.05). No association of prohepcidin with iron parameters was found. Conclusion Significantly lower prohepcidin levels are frequently found in patients with chronic hepatitis B. Levels of this molecule may represent a biochemical correlate of fibrosis in chronic hepatitis C virus infection. Eur J Gastroenterol Hepatol 22:461-465 (C) 2010 Wolters Kluwer Health vertical bar Lippincott Williams & Wilkins.
Keywords: chronic hepatitis B; chronic hepatitis C; histopathology; iron; prohepcidin; IRON STORES; EXPRESSION; INFECTION